Purifikasi Biogas dengan Variasi Ukuran dan Massa Zeolit terhadap Kandungan CH4 dan CO2 - Widhiyanuriyawan, Denny; Hamidi, Nurkholis; Trimandoko, Candra (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2015)
Nowadays, the development of the renewable energy very rapidly. It is driven by the nature of the renewable energy that has been proven to be cleaner than conventional energy, so an increase in the use of renewable energy continues to rise. Biogas is produced from biological processes (anaerobic digester) is capable of producing gas such as CH 4 , CO 2 , H 2 S, and other gases. Therefore it is very important to make the process of refining the biogas. In this research, using the biogas purification process purification method stratified, with a solution of sodium hydroxide with zeolite is purified again and again purified with activated charcoal, hence the storied purification. In this study focused on the observation of zeolite as an adsorbent, the size of the fine and coarse zeolite, and zeolite are varied mass of 50 grams, 100 grams and 150 grams. In 60 minutes, the best result obtained on zeolites fine size with a mass of 150 grams of CO 2 obtained down to 4.07%, but the pressure dropped to 0.65 kPa. With the size of the coarse zeolite at 4.26% CO 2 , with a pressure drop of 0.84 kPa. After the purification process, zeolite proved to be hidrofill with the content of the zeolite fine biggest water with 5.4%.